Relasi Hukum Taurat dan Anugerah dalam Perjanjian Lama - Ndulla, Devanto Kurniawan Hinna; Doloksaribu, Hosea Theopani; Elopore, Wolvy; Hasibuan, Serepina Yoshika (Sekolah Tinggi Teologi Kalvari Manado, 2024)
Abstract: The massive discussion about Torah law in the Old Testament often impacts misinterpreting the Old Testament as Torah religion. This concept continues with the error in understanding salvation which is thought to be based on obedience to the Torah law. This article was created to refute this issue because the concept of salvation in the OT and NT is the same, namely based on God's grace. Therefore, it is necessary to review the relationship between Torah law and grace in the Old Testament. This research uses qualitative methods with a literature study. The author reviews several related literature to explain this concept precisely and biblically. The result obtained is that the Torah is a guide for God's people towards the perfection of salvation in Christ, while grace is the basis for the salvation of God's people. Torah law is implemented as an effort for humans to know God, while grace is given as an effort for God to introduce Himself to humanity. So, the law was passed in response to God's grace that had been poured out for His people. Abstrak: Masifnya pembahasan tentang hukum Taurat dalam Perjanjian Lama seringkali berdampak pada penyalahartian Perjanjian Lama sebagai agama Taurat. Konsep ini berlanjut pada kekeliruan dalam pemahaman tentang keselamatan yang dianggap berdasarkan pada ketaatan menjalankan hukum Taurat. Artikel ini dibuat untuk menyanggah isu tersebut karena konsep keselamatan dalam PL dan PB adalah sama yakni berdasarkan anugerah Tuhan. Oleh sebab itu, perlu diulas mengenai bagaimana relasi hukum Taurat dengan anugerah dalam Perjanjian Lama. Penelitian ini menggunakan metode kualitatif dengan studi kepustakaan. Penulis mengkaji beberapa literatur terkait untuk menjelaskan konsep ini dengan tepat dan alkitabiah. Hasil yang diperoleh adalah hukum Taurat merupakan penuntun agar umat Allah menuju kesempurnaan keselamatan dalam Kristus sementara anugerah adalah dasar keselamatan umat Allah. Hukum Taurat dilaksanakan sebagai upaya manusia mengenal Allah sedangkan anugerah diberikan sebagai upaya Allah memperkenalkan diri-Nya kepada umat manusia. Jadi, hukum Taurat dilakukan sebagai respons atas anugerah Allah yang sudah tercurah untuk umat-Nya